Does physician compensation for declaration of involuntary status increase the likelihood of involuntary admission? A population-level cross-sectional linked administrative database study. Issue 10 (19th July 2021) - Lebenbaum, Michael; Chiu, Maria; Holder, Laura; Vigod, Simone; Kurdyak, Paul
Abstract: Background: There is substantial variability in involuntary psychiatric admission rates across countries and sub-regions within countries that are not fully explained by patient-level factors. We sought to examine whether in a government-funded health care system, physician payments for filling forms related to an involuntary psychiatric hospitalization were associated with the likelihood of an involuntary admission. Methods: This is a population-based, cross-sectional study in Ontario, Canada of all adult psychiatric inpatients in Ontario (2009–2015, n = 122 851). We examined the association between the proportion of standardized forms for involuntary admissions that were financially compensated and the odds of a patient being involuntarily admitted. We controlled for socio-demographic characteristics, clinical severity, past-health care system utilization and system resource factors. Results: Involuntary admission rates increased from the lowest (Q1, 70.8%) to the highest (Q5, 81.4%) emergency department (ED) quintiles of payment, with the odds of involuntary admission in Q5 being nearly significantly higher than the odds of involuntary admission in Q1 after adjustment (aOR 1.73, 95% CI 0.99–3.01). With payment proportion measured as a continuous variable, the odds of involuntary admission increased by 1.14 (95% CI 1.03–1.27) for each 10% absolute increase in the proportion of financially compensated forms at that ED. Conclusions: We found that involuntary admission was more likely to occur at EDs with increasing likelihood of financial compensation for invoking involuntary status. This highlights the need to better understand how physician compensation relates to the ethical balance between the right to safety and autonomy for some of the world's most vulnerable patients.